2018
DOI: 10.1021/acsmedchemlett.8b00501
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of Central Nervous System Penetration by Fatty Acid Amide Hydrolase (FAAH)-Targeted Thyromimetic Prodrugs

Abstract: Thyroid hormone (TH) action is of clinical interest in treating demyelinating diseases of the central nervous system (CNS). Two amide prodrugs of sobetirome, a potent thyroid hormone agonist, were previously shown to significantly improve CNS selective distribution of the parent drug through hydrolysis in the CNS by fatty acid amide hydrolase (FAAH). This concept is elaborated upon here with a series of 29 amide prodrugs targeting FAAH. We identify that conservative aliphatic modifications such as the N-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…In addition to this first-pass metabolic processing, the oral bioavailability of Sob-AM2 is about 5-fold lower than that of sobetirome. The combination of these two issues results in a modest (~2-to 4-fold) increase in CNS sobetirome exposure provided by orally dosed Sob-AM2 compared with the same oral dose of sobetirome (20,42). This is consistent with the modest improvement in rotarod performance we observed in iCKO-Myrf mice treated with 84 μg/kg/d (p.o.)…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition to this first-pass metabolic processing, the oral bioavailability of Sob-AM2 is about 5-fold lower than that of sobetirome. The combination of these two issues results in a modest (~2-to 4-fold) increase in CNS sobetirome exposure provided by orally dosed Sob-AM2 compared with the same oral dose of sobetirome (20,42). This is consistent with the modest improvement in rotarod performance we observed in iCKO-Myrf mice treated with 84 μg/kg/d (p.o.)…”
Section: Discussionsupporting
confidence: 79%
“…We observed significant improvements in rotarod performance and recovery in the iCKO-Myrf model (Figures 4 and 8). Although Sob-AM2 treatment increases sobetirome CNS exposure compared with an equivalent dose of sobetirome by virtue of FAAH activity in the CNS, we have recently found that the magnitude of this distribution depends on the route of administration (42). In addition to being expressed in the CNS, FAAH is also present at high levels in the gastrointestinal tract, especially in rodents (43).…”
Section: Discussionmentioning
confidence: 94%
“…The oral bioavailability of Sob-AM2 is 20% in mice, while that of sobetirome is >90% (Meinig et al, 2019). To confirm that chow administration of either drug provides the anticipated sobetirome levels in vivo, sobetirome concentrations in serum and brain were measured in mice administered chow for 12 weeks at doses of 80 µg/kg sobetirome or 84 µg/kg Sob-AM2 (Devereaux et al, 2018;Placzek et al, 2016;Placzek and Scanlan, 2015).…”
Section: Sob-am2 Lowered Peripheral and Central Vlcfas After Oral Admmentioning
confidence: 99%
“…This study was designed to address this question by using two different strategies to increase thyroid hormone action in the CNS. The first strategy employed Sob-AM2, an amide prodrug derivative of sobetirome that improves distribution of sobetirome to the CNS by 10-fold and increases the brain-to-serum ratio by 60-fold Meinig et al, 2017Meinig et al, , 2019Placzek et al, 2016). Sob-AM2 is converted to sobetirome via hydrolysis by fatty acid amide hydrolase (FAAH), which is highly expressed in the CNS .…”
Section: Introductionmentioning
confidence: 99%
“…15 By targeting this specific enzyme, the prodrug remains masked in peripheral circulation and devoid of receptor activity. 11 The N-methyl amide of sobetirome proved to be the optimal amide for delivering the most sobetirome to the CNS from a systemic dose while at the same time minimizing the peripheral conversion of prodrug to parent drug. 11 However, an open question remained as to whether this prodrug strategy could be successfully employed for other carboxylate drugs that may have therapeutic applications in the CNS.…”
Section: Introductionmentioning
confidence: 99%